Method for preparing ferromagnetic boron nitride nanotube with high Curie temperature through high-temperature catalytic doping
By doping boron nitride nanotubes with samarium Sm ions and using high-temperature catalytic technology, the preparation of high-temperature ferromagnetic boron nitride nanotubes was successfully achieved, solving the problem of difficulty in doping impurity elements in nanotubes in the existing technology. , achieving high-temperature ferromagnetism and optical properties suitable for spin devices.
Patent Information
- Application Number
- CN202410175285.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-02-07
- Publication Date
- 2025-01-24
AI Technical Summary
The prior art is difficult to effectively dopant impurity elements in boron nitride nanotubes to achieve high temperature ferromagneticity, and existing research mainly focuses on hexagonal boron nitride sheets, belts and granular structures, and there is a lack of research on nanotubes.
Through ammonium borate rare earth ion doping synthesis, controlled atmosphere and high-temperature catalytic technology are used to prepare samarium Sm ion-doped hexagonal boron nitride nanotubes. Sm ions not only play a catalytic growth role, but are also doped into the crystal lattice to change the electronic structure. , reduce the energy band gap and achieve high-temperature ferromagnetism.
Successfully prepared a boron nao nano nano-nano-nano-nano-nano-nano-nano-nano-nano-nano-nano-nano-nano nanoma tube with a saturated magnetic intensity between 2.00-5.00MEMU G-1 and the optical band between 2.8-3.5EV to meet the spin in high temperature environments in high temperature environments Device needs and can simulate artificial sudden units.
Smart Images

Figure HDA0004701988000000011 
Figure HDA0004701988000000012 
Figure HDA0004701988000000021
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field related to magnetic materials, and in particular relates to a catalytic doping growth technology related to boron nitride nanotubes. Background Art
[0002] Layered nanotubes are highly anisotropic and are quasi-one-dimensional quantum state structures. Nanotubes with ferromagnetic Curie temperatures above room temperature, while utilizing the charge and spin properties of electrons, are ideal materials for spintronic devices over a wide temperature range. Boron nitride has excellent high-temperature stability and chemical stability, as well as high thermal conductivity and excellent neutron detection properties. Boron nitride nanotubes (BNNTs) have a similar crystal structure to carbon nanotubes. The carbon atoms in carbon nanotubes are mainly sp 2 Hybridization is dominant, with sp 2 and sp 3 The hybrid chemical bonds form highly delocalized large π bonds, and the band gap changes with the diameter and chirality, showing a change from metal to semiconductor. In boron nitride, N and B are sp 2 Hybridization, but the electronegativity of N is much higher than that of B, the electron cloud shrinks to N, forming a highly localized large π bond, resulting in a large band gap, which is independent of the diameter, chirality and number of tube walls of the tube, and leads to the electrical insulation of the material. The prepared boron nitride nanotubes are all insulators with a wide band gap (about 5.5eV). By doping impurity elements in the boron nitride nanotube lattice, changing the electronic structure of the nanotube, reducing the energy band gap, generating spontaneous ferromagnetic order, and utilizing the spin properties of electrons, it will become an excellent carrier for spin devices.
[0003] At present, people have studied the magnetic properties of hexagonal boron nitride by doping, and the research work is mainly based on hexagonal boron nitride sheets, strips and particles. For example, hexagonal boron nitride sheets or strip structures doped with vacancies, fluorine, carbon, oxygen, and Na show ferromagnetism at room temperature and above the Curie temperature. In the study of ferromagnetic boron nitride nanotubes, people found in experiments that fluorination of the surface of boron nitride nanotubes, or coating with other metals, can produce ferromagnetism. However, there are only public reports on the theoretical prediction of the generation of ferromagnetism by impurity doping in the boron nitride nanotube lattice.
[0004] The invention is based on the synthesis of rare earth ion doping of boron nitride nanotube precursor ammonium borate, and utilizes controllable atmosphere and high-temperature catalytic technology to prepare samarium (Sm) ion-doped hexagonal boron nitride nanotubes. The Sm ions not only play a catalytic growth role, but are also doped into the lattice to change the electronic structure, reduce the energy band gap to about 3.0 eV, and achieve a ferromagnetic Curie temperature of more than 700K. Summary of the invention
[0005] The present invention provides a method for preparing high Curie temperature ferromagnetic boron nitride nanotubes by high temperature catalytic doping.
[0006] It is divided into 4 parts: 1) preparing the reaction solution; 2) synthesizing the precursor of boric acid amine doped with samarium Sm ions; 3) preparing boron nitride by catalysis and doping; 4) extracting boron nitride nanotubes;
[0007] The specific steps are as follows:
[0008] 1. Prepare the reaction solution
[0009] Prepare boric acid H3BO3, samarium acetate Sm(C2H3O2)3·4H2O and polyvinylpyrrolidone (C6H9NO) n , PVP three compounds, use deionized water to prepare 0.005 mol / L boric acid solution, and form a clear boric acid aqueous solution by magnetic stirring; measure the Sm element in the samarium acetate compound, and control the molar ratio of samarium Sm ions in samarium acetate to boron B ions in boric acid to be between 0.05-0.12:1, add to the clear boric acid aqueous solution, and stir to form a transparent solution; add polyvinyl pyrrolidone PVP according to 0.1 mg / L, adjust the pH value to 6.1-6.2, and prepare a solution, which is a reaction solution for preparing samarium Sm ion-doped boric acid amine;
[0010] 2. Synthesis of Sm ion-doped borate amine precursor
[0011] The synthetic chemical reaction is completed in a U-shaped synthesis device. The two ports of the U-shaped synthesis device are the reaction material inlet and the tail gas discharge port respectively. Two interfaces are distributed on the top of the reaction material inlet, which are respectively connected to the spiral structure reaction chamber. The bottom of the U-shaped synthesis device is connected to the collection container. The inside of the device is completely sealed. The outer wall of the synthesis device is a closed double-layer structure, which serves as a constant temperature liquid passage. The two interfaces on the top of the reaction material inlet are respectively the inlets of two gasified substances, and the two substances complete chemical reactions in the spiral structure reaction chamber.
[0012] During the synthesis process, the atomized reaction liquid is introduced into the reaction chamber from one interface at the inlet end of the reaction material, and ammonia is introduced into the other interface; the reaction liquid is ultrasonically atomized into 1-5 μm droplets, and the atomized reaction liquid and ammonia are introduced at the same rate, which is controlled at 25-35 mL / min, and the tail gas discharge pressure is 0.2-0.5 mPa; the exhaust volume is 0.1-0.5 m 3 / min; constant temperature control within the temperature range of 55-70°C; atomized reaction liquid and ammonia gas are chemically synthesized in the spiral structure reaction chamber, and the reaction product is collected in the bottom collection container; the reaction product is vacuum dried at 60-80°C to obtain a white granular substance; the substance is samarium Sm ion doped boric acid amine NH4B5O8·4H2O:Sm, which is used as a precursor for preparing boron nitride;
[0013] 3. Boron nitride catalysis and doping preparation
[0014] A high-temperature tube furnace was used to provide a high-temperature environment for the experiment. The prepared samarium Sm ion-doped boric acid amine precursor was placed in a boron nitride porcelain boat. The corundum tube and flange in the tube furnace were effectively sealed. A vacuum pump was used to evacuate the sample to 1х10 -3 Pa vacuum state, then introduce ammonia with a purity of 99.999%; the ammonia flow rate is controlled at 30-40mL / min; the tubular furnace is slowly heated to 1550-1650°C at a rate of 3-5°C per minute, and kept warm for 3-5 hours; then slowly cooled to room temperature of 15-30°C at a rate of 3-5°C per minute; the synthetic substance obtained is a mixture of hexagonal boron nitride h-BN sheets and tubes doped with samarium Sm ions;
[0015] 4. Extraction of Boron Nitride Nanotubes
[0016] The mixture of samarium (Sm) ion-doped hexagonal boron nitride sheets and tubes is immersed in a hydrochloric acid-ethanol solution with a ratio of 36% hydrochloric acid to ethanol of 1:1-1.5 for 7-10 days; the immersed material is washed with deionized water for 3 times, and the sample is vacuum dried at 100-150°C. The sample is placed in an ethanol solution for ultrasonic treatment, and the solution at 1 / 3-2 / 3 in the middle of the container is taken and freeze-dried to obtain a samarium (Sm) ion-doped boron nitride nanotube sample.
[0017] The obtained boron nitride nanotubes have a diameter of 30-60 nm and a length of 20-1000 μm. The content of samarium Sm ions in the boron nitride nanotubes is between 0.40 and 1.60 at.%, and the samarium Sm ions replace part of the B ions in the boron nitride nanotube lattice. The ferromagnetic Curie temperature is between 447 and 477° C., and the saturation magnetization is 2.00-5.00 memu g -1 The optical band gap is between 2.8-3.5eV.
[0018] The boron nitride nanotubes produced by this method can simulate artificial synaptic units.
[0019] Compared with the prior art, the boron nitride nanotubes of the present invention have a ferromagnetic Curie temperature of more than 427°C. (4)
[0020] High-temperature ferromagnetic boron nitride nanotubes meet the needs of high-temperature environments in the field of spin devices; the optical band gap is 2.8-3.5eV; it can realize the basic characteristics of artificial synapses: excitatory postsynaptic current EPSC, paired pulse facilitation PPF and high-pass filtering; the preparation method can meet the requirements of mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of synthesizing samarium (Sm) ion-doped boric acid amine precursor by aerosol condensation chemical deposition method;
[0022] Figure 1In the figure, 1 is an ammonia solution; 2 is a double-necked flask; 3 is a condenser; 4 is a condenser; 5 is ammonia gas; 6 is a precursor solution to be reacted; 7 is an ultrasonic atomizer; 8 is aerosol of the reaction precursor solution; 9 is a condenser; 10 is a condenser; 11 is a samarium Sm ion-doped boric acid amine precursor; 12 is an ultrasonic constant temperature water bath; 13 is a condenser; 14 is waste gas; 15 is an anti-backflow bottle; 16 is an aqueous solution; 17 is an aqueous solution; 18 is the treated waste gas; 19 is a tail gas bottle; 20 is a gas valve switch; 21 is a gas driving device; 22 is a constant temperature circulating water machine; 23 is a constant temperature circulating water; 24 is a constant temperature water bath; 25 is a separating funnel; 26 is a double-necked collecting bottle;
[0023] Figure 2 It is a schematic diagram of a high temperature nitriding device;
[0024] Figure 2 In the figure, 2-1 is a high temperature tube furnace; 2-2 is ammonia gas; 2-3 is a corundum tube; 2-4 is a Sm-doped BN precursor; 2-5 is an anti-backflow bottle; 2-6 is an anti-backflow bottle; 2-7 is an aqueous solution; 2-8 is an anti-backflow bottle; 2-9 is an aqueous solution; 2-10 is waste gas;
[0025] Figure 3 The X-ray diffraction comparison diagram of borate amine precursors with different samarium Sm ion doping concentrations synthesized in Examples 1, 2, and 3;
[0026] Figure 4 X-ray diffraction of boron nitride nanotubes with different samarium Sm ion doping concentrations synthesized in Examples 1, 2, and 3;
[0027] Figure 5 This is a SEM image of the boron nitride nanotube doped with samarium (Sm) ions in Example 2, tested using a scanning electron microscope;
[0028] Figure 6 This is a TEM image of the boron nitride nanotube doped with samarium (Sm) ions in Example 2, tested using a high-resolution perspective microscope;
[0029] Figure 7 This is a FC-ZFC diagram of the boron nitride nanotube doped with samarium (Sm) ions in Example 2, measured using the physical properties comprehensive measurement system PPMS;
[0030] Figure 8 The VSM diagram of the samarium Sm ion-doped boron nitride nanotubes of Example 2, measured by the physical property comprehensive measurement system PPMS, with respect to temperature;
[0031] Fig. 9 The samarium Sm ion doped boron nitride nanotubes of Example 2, the optical band gap measured by ultraviolet visible absorption spectrum using Shimadzu UV-3600 spectrophotometer is Eg=3.0 eV;
[0032] Fig.10 The postsynaptic current (EPSC) of the samarium Sm ion-doped boron nitride nanotubes of Example 2 was measured with different pulse numbers, where C is the number of pulses;
[0033] Fig.11 For the samarium Sm ion doped boron nitride nanotubes of Example 2, paired pulse facilitation (PPF) weight measurement;
[0034] Fig.12 For the samarium (Sm) ion-doped boron nitride nanotubes of Example 2, pulses of different frequencies are used to implement high-pass filter function measurements. DETAILED DESCRIPTION
[0035] The examples are only for more specific explanation of the present invention, and the present invention is not limited to the examples.
[0036] Embodiment 1
[0037] 1. Prepare the reaction solution
[0038] Prepare three compounds of boric acid, samarium acetate and polyvinyl pyrrolidone, the purity of the three compounds is high grade or analytical grade, prepare a 0.005 mol / L boric acid solution with deionized water, and form a clear boric acid aqueous solution by magnetic stirring; measure the Sm element in the samarium acetate compound, and control the molar ratio of samarium Sm ions in samarium acetate to boron B ions in boric acid to be 0.05:1, add to the clear boric acid aqueous solution, and stir to form a transparent solution; add polyvinyl pyrrolidone according to 0.1 mg / L, adjust the pH value to 6.1, and prepare a solution, which is used as a precursor solution for preparing samarium Sm ion doped boric acid amine;
[0039] 2. Synthesis of Sm ion-doped borate amine precursor
[0040] The whole experiment was carried out in a 60℃ constant temperature U-shaped reaction chamber. The reaction liquid was placed in an ultrasonic atomizer for atomization. The atomized reaction liquid and NH3 gas were introduced into the U-shaped reaction chamber at a rate of 30mL / min for reaction. The exhaust gas was exhausted by an exhaust pump. The exhaust gas pressure was 0.3mPa and the exhaust volume was 0.3m 3 / min. The reaction product was collected in a container bottle connected to the lower part of the condenser, and the reactant was vacuum dried at 60°C to obtain white samarium Sm ion-doped boric acid amine NH4B5O8·4H2O:Sm particles, which were used as a precursor for preparing boron nitride;
[0041] 3. Boron nitride catalysis and doping preparation
[0042] A high-temperature tube furnace was used to provide a high-temperature environment for the experiment. The prepared NH4B5O8·4H2O:Sm precursor nanoparticles were placed in a boron nitride porcelain boat, which was effectively sealed by a corundum tube and flange in the tube furnace. A vacuum pump was used to evacuate the corundum tube, and then filled with ammonia gas with a purity of 99.999%. Subsequently, the ammonia flow rate was controlled at 30 mL / min, and the temperature was slowly increased to 1600°C at a rate of 3°C per minute. The mixture was sintered for 3 hours and then slowly cooled to room temperature of 20°C at a rate of 3°C per minute. The synthesized substance was a mixture of hexagonal boron nitride sheets and tubes doped with samarium Sm ions.
[0043] 4 Extraction of boron nitride nanotubes
[0044] The mixture of h-BN sheet and nanotubes was soaked in ethanol hydrochloric acid solution prepared by 36% hydrochloric acid and ethanol in a ratio of 1:1. After soaking for 7 days, it was washed with deionized water for 3 times to remove impurities and dried in vacuum at 100°C. The dried sample was ultrasonicated in an ethanol solution test tube, the intermediate solution was extracted, and freeze-dried to obtain a boron nitride nanotube sample with a Sm doping content of 0.97 at.%, a boron nitride nanotube diameter of 50-60 nm, a length of 20-1000 μm, and a magnetic saturation strength of 4.55 memu g at room temperature. -1 , Curie temperature 447℃, optical band gap 3.3eV.
[0045] Embodiment 2
[0046] 1. Prepare the reaction solution
[0047] Prepare three compounds, namely, boric acid, samarium acetate and polyvinyl pyrrolidone, the purity of the three compounds is high grade or analytical grade, prepare 0.005 mol / L boric acid B(OH)3 solution with deionized water, and form a clear aqueous solution of boric acid B(OH)3 by magnetic stirring; measure the Sm element in the samarium acetate compound, and control the molar ratio of samarium Sm ions in samarium acetate to boron B ions in boric acid at 0.07:1, add to the clear aqueous solution of B(OH)3, and stir to form a transparent solution; add polyvinyl pyrrolidone PVP at 0.1 mg / L, adjust the pH value to 6.1, and prepare a solution, which is used as a precursor solution for preparing samarium Sm ion-doped boric acid amine; 2. Synthesis of samarium Sm ion-doped boric acid amine precursor
[0048] The whole experiment was carried out in a 60℃ constant temperature U-shaped reaction chamber. The reaction liquid was placed in an ultrasonic atomizer for atomization. The atomized reaction liquid and NH3 gas were introduced into the U-shaped reaction chamber at a rate of 30mL / min for reaction. The exhaust gas was exhausted by an exhaust pump. The exhaust gas pressure was 0.3mPa and the exhaust volume was 0.3m 3 / min, collect the reaction product in a container bottle connected to the lower part of the condenser, and vacuum dry the reactant at 60°C to obtain white particles. The product is samarium (Sm) ion-doped boric acid amine particles, which can be used as a precursor for preparing boron nitride;
[0049] 3. Boron nitride catalysis and doping preparation
[0050] A high-temperature tube furnace is used to provide a high-temperature environment for the experiment. The prepared samarium Sm ion-doped boric acid amine precursor is placed in a boron nitride porcelain boat, which is effectively sealed by a corundum tube and flange in the tube furnace. A vacuum pump is used to evacuate the corundum tube into a vacuum state, and then ammonia gas is filled into the tube. The purity of ammonia gas is 99.999%. Subsequently, the ammonia gas flow rate is controlled at 30 mL / min, and the temperature is slowly increased to 1600°C at a rate of 3°C per minute. The mixture is sintered for 3 hours at a temperature of 3°C per minute, and then the temperature is slowly decreased to 20°C room temperature at a rate of 3°C per minute to obtain a mixture of samarium Sm ion-doped hexagonal boron nitride sheets and tubes.
[0051] 4. Extraction of boron nitride nanotubes,
[0052] The mixture of samarium (Sm) ion-doped hexagonal boron nitride sheets and tubes was immersed in an ethanol-hydrochloric acid solution prepared by mixing 36% hydrochloric acid and ethanol in a ratio of 1:1. After immersion for 7 days, the mixture was washed with deionized water for 3 times to remove impurities and dried in a vacuum oven at 100°C. The dried sample was ultrasonically treated in an ethanol solution test tube to extract the intermediate solution and freeze-dried to obtain a boron nitride nanotube sample with a Sm doping content of 1.24 at.%. The boron nitride nanotube had a diameter of 50-60 nm and a length of 20-1000 μm. The magnetic saturation strength of the sample at room temperature was 4.98 memu g -1 , Curie temperature 470℃, optical band gap 3.00eV.
[0053] Embodiment 3
[0054] 1. Prepare the reaction solution
[0055] Prepare three compounds, namely, boric acid, samarium acetate and polyvinyl pyrrolidone, the purity of the three compounds is high grade or analytical grade, prepare a 0.005 mol / L boric acid solution with deionized water, and form a clear boric acid aqueous solution by magnetic stirring; measure the samarium Sm element in the samarium acetate compound, and control the molar ratio of samarium Sm ions in samarium acetate to boron B ions in boric acid to be 0.09:1, add to the clear boric acid aqueous solution, and stir to form a transparent solution; add polyvinyl pyrrolidone PVP according to 0.1 mg / L, adjust the pH value to 6.1, and prepare a solution, which is used as a precursor solution for preparing samarium Sm ion-doped boric acid amine;
[0056] 2. Synthesis of samarium (Sm) ion-doped borate amine precursor.
[0057] The whole experiment was carried out in a 60℃ constant temperature U-shaped reaction chamber. The reaction liquid was placed in an ultrasonic atomizer for atomization. The atomized reaction liquid and NH3 gas were introduced into the U-shaped reaction chamber at a rate of 30ml / min for reaction. The exhaust gas was exhausted by an exhaust pump. The exhaust gas pressure was 0.3mPa and the exhaust volume was 0.3m 3 / min, collect the reaction product in a container bottle connected to the lower part of the condenser, and vacuum dry the reactant at 60°C to obtain white samarium Sm ion-doped boric acid amine NH4B5O8·4H2O:Sm particles, which can be used as a precursor for preparing boron nitride;
[0058] 3. Boron nitride catalysis and doping preparation
[0059] A high-temperature tube furnace was used to provide a high-temperature environment for the experiment. The prepared samarium Sm ion-doped boric acid amine precursor particles were placed in a boron nitride porcelain boat, which was effectively sealed by a corundum tube and flange in the tube furnace. A vacuum pump was used to evacuate the corundum tube, and then filled with ammonia gas with a purity of 99.999%. Subsequently, the ammonia flow rate was controlled at 30 mL / min, and the temperature was slowly increased to 1600°C at a rate of 3°C per minute. The mixture was sintered for 3 hours at a temperature of 3°C per minute, and then slowly cooled to room temperature of 20°C at a rate of 3°C per minute to obtain a mixture of hexagonal boron nitride h-BN sheets and tubes doped with Sm ions.
[0060] 3. Extraction of boron nitride nanotubes,
[0061] The mixture of h-BN sheet and nanotubes was soaked in ethanol hydrochloric acid solution prepared by 36% hydrochloric acid and ethanol in a ratio of 1:1. After soaking for 7 days, it was washed with deionized water for 3 times and dried in vacuum at 100°C. The dried sample was ultrasonicated in an ethanol solution test tube, the intermediate solution was extracted, and freeze-dried to obtain a boron nitride nanotube sample with a Sm doping content of 1.50 at.%, a boron nitride nanotube with a diameter of 50-60 nm and a length of 20-1000 μm. The magnetic saturation strength of the sample at room temperature was 4.38 memu g -1 , Curie temperature 455℃, optical band gap 2.80eV.
Claims
1. A method for preparing high Curie temperature ferromagnetic boron nitride nanotubes by high temperature catalytic doping, characterized in that: The specific steps include: 1) Prepare the reaction solution Prepare boric acid B(OH)3, samarium acetate Sm(C2H3O2)3·4H2O and polyvinylpyrrolidone (C6H9NO) n , PVP three compounds, use deionized water to prepare 0.005 mol / L boric acid solution, and form a clear boric acid aqueous solution through magnetic stirring; measure the Sm element in the samarium acetate compound, and control the molar ratio of Sm ions in samarium acetate to B ions in boric acid to be between 0.05-0.12:1, add it to the clear aqueous solution, and stir it into a transparent solution; add polyvinyl pyrrolidone at 0.1 mg / L, adjust the pH value to 6.1-6.2, and prepare a solution, which is the reaction solution for preparing samarium Sm ion doped boric acid amine; 2) Synthesis of Sm ion-doped borate amine precursor The synthetic chemical reaction is completed in a U-shaped synthesis device. The two ports of the U-shaped synthesis device are the reaction material inlet and the tail gas discharge port respectively. Two interfaces are distributed on the top of the reaction material inlet, which are respectively connected to the spiral structure reaction chamber. The bottom of the U-shaped synthesis device is connected to the collection container. The inside of the device is completely sealed. The outer wall of the synthesis device is a closed double-layer structure, which serves as a constant temperature liquid passage. The two interfaces on the top of the reaction material inlet are respectively the inlets of two gasified substances, and the two substances complete chemical reactions in the spiral structure reaction chamber. During the synthesis process, the atomized reaction liquid is introduced into the reaction chamber from one interface at the inlet end of the reaction material, and ammonia is introduced into the other interface; the reaction liquid is ultrasonically atomized into 1-5 μm droplets, and the atomized reaction liquid and ammonia are introduced at the same rate, which is controlled at 25-35 mL / min, and the tail gas discharge pressure is 0.2-0.5 mPa; the exhaust volume is 0.1-0.5 m 3 / min; constant temperature control within the temperature range of 55-70°C; atomized reaction liquid and ammonia gas are chemically synthesized in the spiral structure reaction chamber, and the reaction product is collected in the bottom collection container; the reaction product is vacuum dried at 60-80°C to obtain a white substance; the substance is Sm ion-doped boric acid amine NH4B5O8·4H2O:Sm, which is used as a precursor for preparing boron nitride; 3) Boron nitride catalysis and doping preparation Using a high-temperature tube furnace, the prepared Sm ion-doped boric acid amine precursor was placed in a boron nitride porcelain boat, and the corundum tube and flange in the tube furnace were effectively sealed; a vacuum pump was used to evacuate the air to 1х10 -3 Pa vacuum state, then introduce ammonia with a purity of 99.999%; the ammonia flow rate is controlled at 30-40mL / min; the tubular furnace is slowly heated to 1550-1650°C at a rate of 3-5°C per minute, and kept warm for 3-5 hours; then slowly cooled to 15-30°C at a rate of 3-5°C per minute; the synthetic substance obtained is a mixture of hexagonal boron nitride h-BN sheets and tubes doped with Sm ions; 4) Extraction of boron nitride nanotubes The mixture of hexagonal boron nitride h-BN sheets and tubes doped with Sm ions is immersed in a hydrochloric acid-ethanol solution with a ratio of 36% hydrochloric acid to ethanol of 1:1-1.5 for 7-10 days; the immersed material is washed with deionized water for 3 times, and the sample is vacuum dried at 100-150°C, the sample is ultrasonically placed in an ethanol solution, and the solution at 1 / 3-2 / 3 in the middle of the container is taken and freeze-dried to obtain a Sm ion-doped boron nitride nanotube sample.
2. The boron nitride nanotubes obtained by the method for preparing high Curie temperature ferromagnetic boron nitride nanotubes by high temperature catalytic doping according to claim 1, characterized in that: The diameter is between 30-60nm, the length is 20-1000μm, the content of samarium Sm ions in the boron nitride nanotubes is between 0.40-1.60at.%, the samarium Sm ions replace part of the B ions in the boron nitride nanotube lattice, the ferromagnetic Curie temperature is between 447-477℃, and the saturation magnetization intensity is 2.00-5.00memu g -1 The optical band gap is between 2.8-3.5eV.
3. The boron nitride nanotubes obtained by the method for preparing high Curie temperature ferromagnetic boron nitride nanotubes by high temperature catalytic doping as claimed in claim 2 are used to simulate artificial synaptic units.